New species and synonymies in Xenopygus Bernhauer (Coleoptera: Staphylinidae: Staphylinini) - Chatzimanolis, Stylianos; Caron, Edilson (Zootaxa, 2016)
Two species are described as new in Xenopygus, X. davidi sp. n. and X. pycnos sp. n. Dysanellus (Leptodiastemus) excellens Bernhauer is transferred to Xenopygus as X. excellens comb. n. and the subgenus Leptodiastemus syn.n. is placed in synonymy with Xenopygus. Xenopygus sancticamillus Caron and Castro syn. n. is shown to be a junior synonym of X. excellens. Gastrisus punctatus Sharp is transferred to Xenopygus as X. punctatus comb. n. Gastrisus cribrum Fauvel syn. n. and X. petilicolis Caron and Castro syn. n. are shown to be junior synonyms of X. punctatus. Two informal species groups are proposed to accommodate the existing species in Xenopygus and an updated key is provided for the identification of the species.